47.2: Invited Paper: 31 inch Rollable OLED Display Fabricated by Inkjet Printing Technology. (24th February 2021) - Gao, Zhuo; Yu, Lei; Li, Zhe; Shi, Wen; Li, Chu; Yuan, Li ge; Sun, Xianwen; Fu, Dong
Abstract : A 31 inch full high definition (FHD, 1920*1080) printed rollable OLED display is fabricated by ink‐jet printing technology and laser lift‐off technology. It is a self‐emitting and top emitting display with oxide TFT backplane. The ink‐jet printing process is optimized by bank pre‐treatment, nozzle auto‐screening and drying process tuning to implement mura‐free display. The prototype rollable TV shows good display quality with a high degree of uniformity and smoothly rollability.